Evaluation of Attention Bias in Morphine and Methamphetamine Abusers towards Emotional Scenes during Early Abstinence: An Eye-Tracking Study - Maryam Soleimannejad; Mehdi Tehrani-Doost; Anahita Khorrami; Mohammad Taghi Joghataei; Ebrahim Pishyareh (Basic and Clinical Neuroscience, 2015)
Introduction: We hypothesized that inappropriate attention during the period of abstinence in individuals with substance use disorder can result in an inadequate perception of emotion and unsuitable reaction to emotional scenes. The main aim of this research was to evaluate the attentional bias towards emotional images in former substance abusers and compare it to healthy adults. Methods: Paired images of general scenes consisting of pleasant, unpleasant, and neutral images were presented to subjects for 3 s while their attentional bias and eye movements were measured by eye tracking. The participants were 72 male adults consisting of 23 healthy control, 24 morphine former abusers, and 25 methamphetamine former abusers. The former abusers were recruited from a private addiction quitting center and addiction rehabilitation campus. The healthy individuals were selected from general population. Number and duration of first fixation, duration of first gaze, and sustained attention towards emotional scenes were measured as the main variables and the data were analyzed using the repeated measures ANOVA. Results: A significant difference was observed between former morphine abusers and healthy control in terms of number and duration of first fixations and first gaze duration towards pleasant images. Discussion: Individuals with morphine use disorder have more problems with attending to emotional images compared to methamphetamine abusers and healthy people.